Viral hepatitis and Treponema pallidum prevalence in persons who underwent premarital blood tests in Argentina - Angeleri, Patricia (2019)
The objective of this study was to estimate the prevalence of different serological markers of hepatitis A, B and C viruses and Treponema pallidum among the adult population of Argentina. To achieve this, adults who attended health services for premarital exams (which are mandatory and includes screening for syphilis) were recruited. A cross-sectional study was designed with a cluster sampling strategy. Couples who attended selected health services for premarital screening between 2013 and 2014 in Buenos Aires, Cordoba, Mendoza and Santa Fe provinces were included. A total of 3833 individuals were recruited. Anti-HAV prevalence was 63.9%, anti-HCV 0.3%, anti-HBc (without HBsAg) 1.9%, HBsAg 0.3%, and T pallidum 0.8%. Anti-HAV was higher among older participants, foreigners and those from the lower strata. HBV increased with age and was higher among foreigners and those with lower formal educational level. Anti-HCV frequency increased with age. Premarital screening of viral hepatitis could constitute an instance of diagnosis, vaccination and inclusion in care of those in need. Results from this study will allow the national hepatitis programs to design public policies in order to diminish the impact of these infections on the population.